2020
DOI: 10.1103/physrevx.10.021010
|View full text |Cite
|
Sign up to set email alerts
|

Field-Angle-Resolved Magnetic Excitations as a Probe of Hidden-Order Symmetry inCeB6

Abstract: In contrast to magnetic order formed by electrons' dipolar moments, ordering phenomena associated with higher-order multipoles (quadrupoles, octupoles, etc.) are more difficult to characterize because of the limited choice of experimental probes that can distinguish different multipolar moments. The heavy-fermion compound CeB 6 and its La-diluted alloys are among the best-studied realizations of the long-range-ordered multipolar phases, often referred to as "hidden order". Previously the hidden order in phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 75 publications
(153 reference statements)
1
18
0
Order By: Relevance
“…The measurements were done using cold-neutron triple-axis spectrometers PANDA at the FRM-II research reactor of the Maier-Leibnitz Zentrum (MLZ, Garching, Germany) [50,51] and 4F2 at the reactor Orphée of the Laboratoire Léon Brillouin (LLB, CEA-Saclay, France), in addition to the spectroscopic measurements described in Ref. 52. Energy analysis was used to eliminate the contribution from inelastic scattering, revealing purely elastic Bragg intensity at q 1 = 1 It has to be noted that due to the geometric constraints of the triple-axis experiment, not every ordering vector can be reached for certain field directions.…”
Section: A Elastic Neutron Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were done using cold-neutron triple-axis spectrometers PANDA at the FRM-II research reactor of the Maier-Leibnitz Zentrum (MLZ, Garching, Germany) [50,51] and 4F2 at the reactor Orphée of the Laboratoire Léon Brillouin (LLB, CEA-Saclay, France), in addition to the spectroscopic measurements described in Ref. 52. Energy analysis was used to eliminate the contribution from inelastic scattering, revealing purely elastic Bragg intensity at q 1 = 1 It has to be noted that due to the geometric constraints of the triple-axis experiment, not every ordering vector can be reached for certain field directions.…”
Section: A Elastic Neutron Scatteringmentioning
confidence: 99%
“…Energy analysis was used to eliminate the contribution from inelastic scattering, revealing purely elastic Bragg intensity at q 1 = 1 It has to be noted that due to the geometric constraints of the triple-axis experiment, not every ordering vector can be reached for certain field directions. The measurement is restricted to wave vectors in the horizontal scattering plane, while the field direction is vertical in all our measurements [52]. Therefore, q 1 can be probed in all four high-symmetry configurations (but not at intermediate angles), q 2 is only accessible for B [111] and [110], and q AFQ only for B [110] and [112].…”
Section: A Elastic Neutron Scatteringmentioning
confidence: 99%
“…CeB 6 is known to have a typical dense Kondo compound behaviour and a complex magnetic phase diagram [44][45][46][47]. Cerium hexaboride exhibits Kondo-like behaviour and has a Kondo temperature of T K = 19 K. Upon cooling, CeB 6 undergoes two magnetic ordering transitions: the first to a state in which antiferroquadrupolar and field-induced octupolar order coexist, below T Q = 3.2 K, and then to an antiferromagnetic ordering of the Ce dipoles, below T N = 2.3 K. Moreover, a subsequent study reported a new transition, of unknown origin, at T 2 = 1.6 K [45].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress, e.g., the discovery of the coexistence of an unusual metallic surface state and an insulating bulk state in SmB 6 [19,48] and the observation of the long-range-ordered multipolar phases in CeB 6 [47], has generated new interest in these materials. One route towards the investigation of the exotic metallic surface state arising in SmB 6 and understanding of its topological nature, is through chemical substitution in this TKI with other rare earth ions.…”
Section: Introductionmentioning
confidence: 99%
“…to residual quasiparticle interaction heavy-fermion metals are prone to instabilities resulting, as in the above compounds, in exotic low-temperature magnetic, multipolar [6,7], and superconducting phase transitions [8]. In rare cases like the much discussed SmB 6 or YbB 12 borides [9] the chemical potential resides inside the hybridization gap leading to a Kondo insulator or semiconductor state (in the former due to the mixed valence [10] of ≈2.5+, it should be better termed mixed valence or hybridization gap insulator).…”
mentioning
confidence: 99%